Dissolved inorganic carbon, pH, alkalinity, temperature, salinity and other variables collected from discrete sample and profile observations using Alkalinity titrator, CTD and other instruments from HUDSON in the Davis Strait, Labrador Sea and North Atlantic Ocean from 2014-05-02 to 2014-05-24 (NCEI Accession 0157623) - Azetsu-Scott, K., and I. Yashayaev (NOAA NCEI Environmental Data Archive, 2016)
NCEI Accession 0157623 includes chemical, discrete sample, physical and profile data collected from HUDSON in the Davis Strait, Labrador Sea and North Atlantic Ocean from 2014-05-02 to 2014-05-24. These data include AMMONIUM (NH4), CHLOROFLUOROCARBON-12 (CFC-12), DISSOLVED INORGANIC CARBON (DIC), DISSOLVED OXYGEN, HYDROSTATIC PRESSURE, NITRATE, NITRITE, SALINITY, SULFUR HEXAFLUORIDE (SF6), TOTAL ALKALINITY (TA), WATER TEMPERATURE, pH, phosphate and silicate. The instruments used to collect these data include Alkalinity titrator, CTD, Coulometer for DIC measurement, bottle and spectrophotometer. These data were collected by Kumiko Azetsu-Scott and Igor Yashayaev of Bedford Institute of Oceanography as part of the GOSHIP_AR07W_2014 data set. CDIAC associated the following cruise ID(s) with this data set: GOSHIP_AR07W_2014 and HUD2014007 The International CLIVAR Global Ocean Carbon and Repeat Hydrography Program carries out a systematic and global re-occupation of select WOCE/JGOFS hydrographic sections to quantify changes in storage and transport of heat, fresh water, carbon dioxide (CO2), and related parameters.